The effect of bacterial overgrowth syndrome and bacterial translocation on the course of liver cirrhosis - M. S. Zharkova; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine the effect of bacterial overgrowth syndrome and translocation of bacterial DNA in ascitic fluid on morbidity in liver cirrhosis (LC) and long-term life expectancy.Material and methods. Overall 42 LC patients were included to original study (Child-Pugh class A – 15 patients, class B – 10, class C – 17). For diagnostics of bacterial overgrowth syndrome in the bowel hydrogen breath test was carried out. Possible bacterial translocation from intestine to ascitic fluid was assessed by the presence of bacterial DNA by PCR method. For 12 months patients were monitored to assess their life prognosis. Data were processed by «SPSS», version 13.0 software.Results. Bacterial overgrowth syndrome was revealed in 69% (29 of 42) patients with LC (46,7% – class A, 60,0 % – class B and 94,1% – class C, р=0,013). This syndrome was diagnosed mostly in patients with ascites (84,0%) in comparison to those without (47,1%, р=0,017). Correlation between bacterial overgrowth syndrome and stage of varicose dilation of esophageal veins (р=0,001) was revealed. Hypotension and tachycardia, infections were present in patients with positive hydrogen breath test (р<0,036) more often. The survival rate for 12 months in the group of patients with bacterial overgrowth syndrome was lower in comparison to patients without bacterial overgrowth (51,7% vs 84,6% respectively, р<0,042). Among patients with tense ascitis (n=16) bacterial DNA in ascitic fluid was detected in 9 cases (56,3%). Ascitis, resistant to diuretic therapy was more frequent in patients with bacterial translocation (66,7%) in comparison to patients without it (14,3%) [OR 4,667; 95%CI: 0,717–30,353; р=0,036]. All patients with infected ascitis (n=5) had bacterial DNA, though etiological agent was found at culture only in one.Conclusion. In patients with liver cirrhosis bacterial overgrowth syndrome is associated with portal hypertension, hemodynamic disorders, infections. It acts as one of prognostic factors of low survival rate in such patients. The course of disease in LC patients with tense ascitis and bacterial translocation is complicated by development of diuretic-resistant ascitis and ascitic fluid infection most often.